Analisis Kapasitas Tampung Saluran Drainase dalam Menampung Debit Limpasan Hujan pada Wilayah Penjaringan Asri, Surabaya - Arum Dewi Cahyani; Saves, Faradlillah (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Penjaringan Asri Street often experiences flooding during high rainfall due to land conversion, residential growth, and blockage of drainage channels by garbage, sedimentation, and wild vegetation. High population density reduces infiltration areas so that runoff discharge increases and exceeds the channel capacity. This study aims to assess the capacity of drainage channels to accommodate design flood discharge with return periods of 2, 5, and 10 years. The data used include the results of channel measurement surveys, rainfall for the period 2014–2024, and topographic maps. Hydrological analysis was carried out using the Thiessen Polygon method, Log Pearson III Distribution, and the Rational Method. Based on the analysis results, the design flood discharge for each return period shows that the 2-year return period is 2,069 m3/second, the 5-year return period is 2,439 m3/second, and the 10-year return period is 2,640 m3/second. Meanwhile, based on the comparison of the design discharge (Qhydrology) with the hydraulic capacity (Qhydraulic), all channels exhibited flood conditions for return periods of 2 years, 5 years, and 10 years. This is due to the higher Qhydrology value compared to Qhydraulic, indicating that the existing channel cross-sectional capacity is unable to accommodate the design flood discharge. Therefore, it can be concluded that the channels in the Penjaringan Asri area are not yet capable of accommodating the design flood discharge. Therefore, channel capacity increases and routine maintenance are required to ensure the system functions optimally in reducing flooding.